2018
DOI: 10.1002/ps.5135
|View full text |Cite
|
Sign up to set email alerts
|

iTRAQ‐based quantitative proteome revealed metabolic changes of Sitophilus zeamais in response to terpinen‐4‐ol fumigation

Abstract: Metabolic changes indicated that terpinen-4-ol could affect the energy supply and potentially be metabolized and detoxified by various enzymes in S. zeamais. The results provide a foundation for further functional studies of key proteins mediated by terpinen-4-ol. © 2018 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 53 publications
0
11
1
Order By: Relevance
“…Insect P450s were found in all tissues and performed important functions such as the degradation of drugs, pesticides, and plant secondary metabolites. 39,40 Genomes of different insects have revealed dynamic changes in the number of CYP genes, ranging from 37 in the body louse Pediculus humanus to 204 in the mosquito Culex quinquefasciatus. [41][42][43] In this study, 66 P450s with complete ORFs were identified and named from the transcriptome of M. separata integument.…”
Section: Discussionmentioning
confidence: 99%
“…Insect P450s were found in all tissues and performed important functions such as the degradation of drugs, pesticides, and plant secondary metabolites. 39,40 Genomes of different insects have revealed dynamic changes in the number of CYP genes, ranging from 37 in the body louse Pediculus humanus to 204 in the mosquito Culex quinquefasciatus. [41][42][43] In this study, 66 P450s with complete ORFs were identified and named from the transcriptome of M. separata integument.…”
Section: Discussionmentioning
confidence: 99%
“…After removal of the puparium, the whole body of the pupa was disrupted in a lysis buffer (8 M urea, 40 mM Tris-HCl with 1 mM phenylmethane sufonyl fluoride, 2 mM EDTA and 10 mM dithiothreitol, pH 8.5) with a protease inhibitor by TissueLyser (Huang et al, 2018). After centrifuging at 25,000 g for 20 min, the supernatant was carefully removed and mixed with 5 vol of cold acetone and stored at −20°C overnight.…”
Section: Methodsmentioning
confidence: 99%
“…The IPEC-J2 cells were frozen with liquid nitrogen immediately and then lysed in the “lysis buffer (8 M Urea, 40 mM Tris–HCl with 1 mM PMSF, 2 mM EDTA, and 10 mM DTT, pH 8.5)” (Li et al, 2018). “After centrifugation at 25,000 g at 4°C for 20 min, the supernatant obtained was reduced with 10 mM DTT at 56°C for 1 h, and then alkylated with 55 mM iodoacetamide (IAM) in the dark at room temperature for 45 min” (Huang et al, 2018). Following further centrifugation with 25,000 g at 4°C, the supernatant was quantified by Bradford method.…”
Section: Methodsmentioning
confidence: 99%